FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN KELUHAN GANGGUAN PERNAFASAN PADA PEKERJA BATU BATA DI DESA TALANG BELIDO KECAMATAN SUNGAI DELAM KABUPATEN MUARO JAMBI TAHUN 2021 - Muhammad Ainurrazaq; Abul Ainin Hapis; Hamdani Hamdani (Sekolah Tinggi Pariwisata Mataram, 2022)
Abstract Brick workers are one of the workers who are at risk of experiencing respiratory problems. This is due to exposure to dust generated during the combustion process. Talang Belido Village is the center of brick business in Sungai Gelam District. Based on the initial survey, 60% of eye stone workers in Talang Belido Village have respiratory problems. The purpose of the study was to determine the factors associated with respiratory complaints in brick workers. The research design used a cross sectional design. The research sample is 50 brick workers in Talang Belido Village. The sampling technique used was total sampling technique. This research was conducted in August 2021 in Talang Belido Village. The research instrument is a questionnaire. Data collection techniques by means of interviews and observations. Data were analyzed by univariate and bivariate using chi square test. As many as 63.2% of respondents have complaints of respiratory problems, 57.9% of respondents have long working periods, 52.6% of respondents work with risky length of work, 52.6% of respondents do not use PPE and 63.2% of respondents smoke. Bivariate results showed that there was a relationship between years of service (p=0.000), length of work (p=0.001), use of PPE (p=0.000) and smoking habits (p=0.000) with complaints of respiratory problems among brick workers in Talang Belido Village. . It is expected that brick workers always use PPE at work, reduce the number of cigarettes they consume, work according to working hours..